Gelati Ilmu: The Educational Game in Banten-Dialect Javanese Language for Learning Media of Fourth Grade Students - Hasanah, Huswatun; Masum; Hilmi, Tubagus Wildan (International Journal of Elementary Education, 2023)
Banten-Dialect Javanese Language is one of the most difficult subjects, according to the 4th grade elementary school students. This situation is caused by several factors, namely motivation, environment, mother tongue, surrounding culture, as well as the boring and less innovative instructional media. The study aims to develop a quality educational game as an alternative learning media for the Banten-Dialect Javanese Language subject. This type of research is development. The study used the ADDIE model as a development method. This educational game had been validated by 1 material experts and 1 media expert. The experiment subjects were 4th grade students collected 30 students. Data collected methods are observation, interviews, and questionnaires. The technique of analysing the data is descriptive qualitative and quantitative analysis. The results of validity test by material experts were 94.44% (very good) and by media experts, namely 83.92% (very good), so it is said to be valid. Student responses in the small group test obtained a proportion of 77,25% (agree) so it is said to be practical. The results of this study indicated that the educational game, Gelati Ilmu, is feasible to be used as an alternative learning media for the Banten-Dialect Javanese Language subject.